2017
DOI: 10.1007/s10018-017-0203-8
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in global environmental performance: assessing heterogeneity

Abstract: This paper examines convergence in environmental/carbon performance by constructing a measure based on production theory, where production processes explicitly result in the production of two outputs; a good output (GDP) and a bad output (CO 2 ). We use the derived measure to test the b-convergence hypothesis for a panel of 94 countries. The results reveal evidence in support of b-convergence in environmental, or carbon performance for the entire (global) sample and each of the sub-samples. The evidence points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Energy produced from fossil fuels has an adverse effect on environmental performance and public health in both middle and high‐income countries . However, the anticipated advances from energy efficiency or renewables could reduce carbon dioxide emissions (CO 2 ) and energy costs to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Energy produced from fossil fuels has an adverse effect on environmental performance and public health in both middle and high‐income countries . However, the anticipated advances from energy efficiency or renewables could reduce carbon dioxide emissions (CO 2 ) and energy costs to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Energy generated from fossil fuels may lead to environmental degradation in both middle and high-income countries. 14 Therefore, the expected development from energy efficiency or renewable could dwindle CO 2 emissions and energy costs to consumers. According to a report by REN21, the share of renewable energy in total global energy (final b energy) has reached to almost 20% and its largest part is basically produced from hydropower (15.5%), wind power (34%) and photovoltaic (47%).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, by using the annual data obtained over the period 1980-2013, the authors concluded that although some states exhibited convergence, some other states exhibited divergence. Unlike previous studies, Brännlund and Karimu (2018) for those countries. The study, which also investigated whether the β convergence was valid, found that the β convergence was valid for developed countries; whereas was not valid for developing countries.…”
Section: An Overview Of the Convergence Literaturementioning
confidence: 74%